Essays on Halakhah in the New Testament - Jackson, Bernard S. (Jewish and Christian perspectives series, 2008)
The texts of the New Testament have long been understood to require interpretation in the light of the Hebrew Bible, Qumran and other postbiblical literary and documentary sources. Conversely, they provide an invaluable source for the reconstruction of ""halakhah"" in the late Second Commonwealth period. These essays illustrate the complexity of the inter-relationships, and the methodological issues which arise: the ""legal"" content of the texts cannot be separated from the intertextualities of Jewish theology. The topics cover letter and spirit, prophecy and law, forgiveness, the accounts of